Ahmad Rashid Talu the Pioneer of the Renewal of Malay Site Literature in 1889-1939 - Lasrita Lasrita; Azmi Fitrisia (Science and Environmental Journal for Postgraduate, 2021)
Ahmad Rashid Talu Pioneer of Renewal of Malaysian Malay Literature 1889-1939, ideas that underline Ahmad Rashid Talu’s creative process, image and thought. The concept that underlies the creation of Ahmad Rashid Talu’s literary works is his persistence in changing society and the nation by carrying out a movement of change and renewal by writing, nemely literary works in the from of novels. Ahmad Rashid Talu made direct observations of every area he visited while traveling ini Malay Malaysia. Then literary works are written based on imagination and feelings that reveal various social diseases that occur in people’s lives which are motivated by socio-culture. Every literary work contains an open messange to pursue the progress of the Malay nation or state of Malaysia.